2022
DOI: 10.1097/yct.0000000000000858
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Treatment Utilization for Inpatient Management of Catatonia in Adolescents With Schizophrenia Spectrum Disorders

Abstract: ObjectiveThe aim of this study was to determine rates of electroconvulsive therapy (ECT) use for catatonia in schizophrenia spectrum disorders, stratified by patient demographics and hospital characteristics, and its impact on inpatient length of stay and cost.MethodsWe found 155 adolescents (aged 12–18 years) with principal discharge diagnosis of schizophrenia spectrum disorders with catatonia from the National Inpatient Sample. They were subgrouped into ECT (n = 20) and non-ECT (n = 135) groups. We used desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…ECT also has a positive effect on the clinical response of adults with treatment-resistant SCZ (4). A trial determined the rates of ECT used in adolescents with catatonia in schizophrenia spectrum disorders in America, the results suggested that ECT was used for only 13% of adolescents with catatonia when comorbid schizophrenia spectrum disorders, and a high rate of ECT use was evident for Whites compared with the other race and also was seen in private health insurance beneficiaries (5). These characteristics in the utilization of ECT in adolescents were also found by Trivedi et al (6).…”
Section: Introductionmentioning
confidence: 99%
“…ECT also has a positive effect on the clinical response of adults with treatment-resistant SCZ (4). A trial determined the rates of ECT used in adolescents with catatonia in schizophrenia spectrum disorders in America, the results suggested that ECT was used for only 13% of adolescents with catatonia when comorbid schizophrenia spectrum disorders, and a high rate of ECT use was evident for Whites compared with the other race and also was seen in private health insurance beneficiaries (5). These characteristics in the utilization of ECT in adolescents were also found by Trivedi et al (6).…”
Section: Introductionmentioning
confidence: 99%
“…2 We also present 2 articles on the use of ECT in vey psychiatrically ill adolescents, finding that young patients respond well to ECT, 3 but those adolescents with catatonia are often not offered this effective treatment. 4 At the other end of the age spectrum, we learn that nonresponse to ECT in depressed older people may still be followed by remission to other treatments in 24.5% of cases of nonresponse over the subsequent 2 years. 5 This is in line with the earlier work showing that 16% of persons with depression who failed a course of ECT eventually remitted by other means of treatment over the next 6 months.…”
mentioning
confidence: 99%
“…In parallel, this issue of the journal describes recommended guidelines for the pre-ECT evaluation 2 . We also present 2 articles on the use of ECT in vey psychiatrically ill adolescents, finding that young patients respond well to ECT, 3 but those adolescents with catatonia are often not offered this effective treatment 4 . At the other end of the age spectrum, we learn that nonresponse to ECT in depressed older people may still be followed by remission to other treatments in 24.5% of cases of nonresponse over the subsequent 2 years 5 .…”
mentioning
confidence: 99%